(untitled) (World Bulletin of Management and Law, 2024)
This article emphasizes the main concepts related to the implementation of digital control in trust management, the powers of state authorities in the implementation of digital control. Also, specific issues related to ensuring the security of a person’s assets after his death and maintaining his digital security are emphasized